Analisis Hubungan Jarak Rumah dengan Angka Kepadatan Lalat di Lingkungan Peternakan Ayam Petelur - Jatmikowati, Hesti; Isworo, Tirta Amerta; Hidayat, Arief Maulana; Sacharum, Nofilia; Khotimah, Khusnul; Nuriana, Nuzula Irfa (Universitas Nurul Jadid, 2025)
The existence of vectors is still a problem regarding the status and level of health in Indonesia. In Mayang Village, there is a chicken farm that is located less than 250 meters from the residential area. The location of the chicken farm that is not in accordance with the housing will have an impact on the very high density of flies in the enviromental. This research is a quantitative research, analytical research design and cross sectional design, because it aims to analyze the relationship between house distance and fly density levels as well as an observational approach. The population of this study was 409 and a sample of 80 houses was obtained using the Slovin formula. Measuring fly density is done using a fly grill tool. The research results fly density measurements were carried out in zone 2 for 47 houses (58.8%). The low category was found by 37 (46.3%). The existence of a relationship between the distance from the house and the level of fly density can be shown by the significance value of p-value (0.000) and CC (0.641) which means a strong relationship, meaning that the closer the house is to the farm, the higher the fly density. Based on the research results, for people who want to build a livestock business, they must choose a location for the pen that is far from residential areas, in accordance with the SOP, namely a minimum of 250 meters, so as not to reduce environmental quality.